The Effect of Credit Quality on Profitability: Study on A Mortgage in Garut City - Meira Meilawati; Indah Damayanti; Lungguh Jatmika (Acman: Accounting and Management Journal, 2023)
This study aimed to determine and analyze the effect of credit quality on profitability in one of the mortgages in Garut City. The research method is quantitative, with a descriptive and verification analysis approach. The data used are five-year financial reports from 2016 to 2020. The study results show that the general description of Non-Performing Loans (NPL) and Profits is not optimal; non-performing Loans (NPL) correlate with Profits of 0.796, simple linear regression results that Y = -15.063 + 0.549. Non-performing Loans influence profit (Y) of 0.634 or 63.4%.